Beneficial Effect of Water-Based Exercise Training on Exercise Capacity in COPD Patients—a Pilot Study - Charususin, Noppawan; Sricharoenchai, Thiti; Pongpanit, Karan; Yuenyongchaiwat, Kornanong; Namdaeng, Phuwarin; Laosiripisan, Jitanan; Keawutan, Piyapa (Frontiers in Rehabilitation Sciences, 2021)
Background: Chronic obstructive pulmonary disease (COPD) is a common, preventable, and treatable condition, characterized by persistent airflow limitation. Exercise training is a core component of pulmonary rehabilitation in people with COPD. Water-based exercise has been studied, but it remains unclear whether water-based exercise program leads to the improvement in respiratory function, muscle strength, balance ability, and exercise capacity. We aim to study the effect of an 8-week water-based exercise program on respiratory function, muscle strength, balance ability, and exercise capacity in people with COPD. Methods: Fourteen stable COPD participants (FEV1 56.8±24.6%pred) were recruited and randomized into a water-based exercise or a land-based exercise group. Both groups were trained for 8 weeks, two-session per week. Pulmonary function, respiratory muscle strength, peripheral muscle strength, balance ability, exercise capacity [six-minute walking test (6MWT), incremental shuttle walk test (ISWT), and endurance shuttle walk test (ESWT)] were assessed at baseline and at the end of the program. ANCOVA was used to conduct between-group comparisons of outcomes after adjusting for pre-intervention values. Results: Baseline characteristics of participants were not significantly different between the two groups (p≥0.05). After the 8-week training program, participants in the intervention group achieved larger gains in ESWT (Δ663.4 ± 279.5 vs Δ45.4 ± 93.2 seconds, p=0.001). In addition, maximal inspiratory pressure (MIP) was significantly increased more in the intervention group (Δ11.1 ± 7.8 vs Δ1.1 ± 5.7 cmH2O, p=0.026). However, no significant differences in pulmonary function, peripheral muscle strength, balance ability variables, 6MWD (p=0.248) and ISWT (p=0.506) were observed between the two groups. Conclusions: The water-based exercise program could be recommended to the COPD rehabilitation program for improving the endurance exercise capacity and inspiratory muscle strength. Clinical trial registration number TCTR20210125005 (https://www.thaiclinicaltrials.org)